Runt-Related Transcription Factor 3 Promotes Acute Myeloid Leukemia Progression - Zhang, Wenwen; Ma, Qian; Long, Bing; Sun, Zhangyi; Liu, Lingling; Lin, Dongjun; Zhao, Minyi (Frontiers in Oncology, 2021)
Acute myeloid leukemia (AML) is an aggressive hematological malignancy with high relapse/refractory rate. Genetic and epigenetic abnormalities are driving factors for leukemogenesis. RUNX1 and RUNX2 from the Runt-related transcription factor (RUNX) family played important roles in AML pathogenesis. However, the relationship between RUNX3 and AML remains unclear. Here, we found that RUNX3 was a super-enhancer-associated gene and highly expressed in AML cells. The Cancer Genome Atlas (TCGA) database showed high expression of RUNX3 correlated with poor prognosis of AML patients. We observed that Runx3 knockdown significantly inhibited leukemia progression by inducing DNA damage to enhance apoptosis in murine AML cells. By chromatin immunoprecipitation sequencing (ChIP-seq) analysis, we discovered that RUNX3 in AML cells mainly bound more genes involved in DNA-damage repair and antiapoptosis pathways compared to that in normal bone marrow cells. Runx3 knockdown obviously inhibited the expression of these genes in AML cells. Overall, we identified RUNX3 as an oncogene overexpressed in AML cells, and Runx3 knockdown suppressed AML progression by inducing DNA damage and apoptosis.